The Composition of a Rigor without Organs through an Opera of Aberrant Movements - Gomes, Danilo Olimpio; Miarka, Roger [UNESP] (Univ Pedagogica & Tecnologica Colombia, 2024)
This article proposes to take on speeches expressed about rigor, multiplying them into possibilitiesto produce the concept of rigor without organs. To do this, it uses the discursive remains aboutrigor enunciated in a Real Analysis discipline and the exercise of problematization and productionof the concept of rigor without organs, using tools from the philosophies of differences. For theaesthetic proposal, an opera structure was chosen as a political form of narrative experimentation.As research results, the concept of rigor without organs is produced to shift the rigor of itsdimension of power towards a rigor of the event, which operates through escapes in singularizedand aberrant movements, in accordance with an operating rule, more as a weapon for theinvention of other forms of life in a relationship with rigor than as a tool for reproducing relationships (of power) with rigor.
Keywords: body without organs; philosophies of difference; mathematical education; real analysis; power relations